POLA PENYELESAIAN KEKERASAN DALAM RUMAH TANGGA PADA WANITA JAWA DI YOGYAKARTA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRACT The research aim is to know the pattern of problem solving about domestic violence among Javanese women in Yogyakarta. Data collecting was done by a questionnaire (open-ended and closed questions). The collected data was analyzed qualitatively. The research was held among 56 Javanese married women in Yogyakarta, who living together with their spouses. Respondents selection were based from educational characteristics, and occupational status. Samples of the research area were determined by purposive sampling in Sleman, Bantul and Kodia Yogyakarta. The result of this research shows that domestic violence is an abuse of husband to wife includes physical, mental, sexual and economical. If they suffer the problem, they tend to hide and keep silent because of cultural influence. There are two pattern of solving of domestic violence namely help seeking such as going to NGO, report to police or going to doctor and no help seeking because of trying to communicate to the partner, silent, and crying.